1982
DOI: 10.1111/j.1471-0528.1982.tb05058.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress hormones and placental steroids in physical exercise during pregnancy

Abstract: The hormonal responses to exercise during later pregnancy were studied in relation to an exercise test in ten healthy women. At the end of the 10-min exercise, maternal heart rate had risen from 9 3 i 3 -2 (meankSEM) to 157k6.3 beats/min, and systolic blood pressure from 120k3.4 to 148k5.4 mmHg, but diastolic blood pressure was unchanged. Plasma concentrations of noradrenaline and adrenaline rose rapidly during the exercise, from 2 . 9 k 0 . 3 to 6 . 9 k 1 -2 nmol/l and from 0,31+0.04 to 0,47+0.08 nmol/l respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…there is a greater activation of sympathetic nerves than the adrenal medulla (8). In this study, a similar response has been found in pregnant women consistent with the results of other workers (6,9). The detected decrease in noradrenaline with increasing gestation may be due to a dilutional effect from the continued expansion by approximately 15% of plasma volume from midpregnancy until the 32nd week of gestation.…”
Section: Discussionsupporting
confidence: 92%
“…there is a greater activation of sympathetic nerves than the adrenal medulla (8). In this study, a similar response has been found in pregnant women consistent with the results of other workers (6,9). The detected decrease in noradrenaline with increasing gestation may be due to a dilutional effect from the continued expansion by approximately 15% of plasma volume from midpregnancy until the 32nd week of gestation.…”
Section: Discussionsupporting
confidence: 92%
“…The role of catecholamines has been debated (7,8). Physical exercise during pregnancy has been shown to release both adrenaline and noradrenaline (8,9), but little is known about the correlation between catecholamines and uterine or placental blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of physical activity on E 3 level of pregnant women is controversial. Some reported that E 3 level after exercise was increased and other reported it was decreased after an increase 38,39) . In this study, urinary E 3 level of the pregnant subjects seems to be lower during physical activity or work rather than at rest.…”
Section: Ementioning
confidence: 99%